The war of the roses: demilitarizing invasion biology. Issue 9 (1st November 2005) - Larson, Brendon MH
Abstract : Biologists need to continuously reflect upon the ethical and rhetorical dimensions of their language when communicating about invasive species. In particular, is current language likely to promote social cohesion and, consequently, effective and appropriate action towards invasive species? To address this question, I focus on prevailing militaristic and combative metaphors within invasion biology. I argue that these metaphors are problematic because (1) they lead to an inaccurate perception of invasive species; (2) they contribute to social misunderstanding, charges of xenophobia, and loss of scientific credibility; and (3) they reinforce militaristic patterns of thought that are counterproductive for conservation. Therefore, while these metaphors may effectively motivate conservation action in the short term, they could be ineffective in the long term. Alternatives to militarism will better promote realistic management and conservation goals in a multicultural context.